Optimal office lighting use: a Swedish case study. Issue 9 (6th July 2015) - Maleetipwan-Mattsson, Pimkamol; Laike, Thorbjörn
Abstract : Purpose: – The purpose of this paper is to determine the optimal office lighting use with different types of lighting controls to achieve energy savings and provide visual comfort for individuals. Design/methodology/approach: – A case study and field measurements were carried out in 18 single-occupancy offices in Sweden where six different lighting controls were investigated. Occupancy and daylight hours were key issues for determining the lighting use. For each office, occupancy patterns, use of a ceiling luminaire, energy usage and perceptions of office lighting in the spring-summer and autumn-winter were established. Findings: – The use of luminaires varied among the occupants and could be habitual. Though the study yielded positive results concerning the potential for manual or daylight dimming with occupancy switch-off controls to increase optimal lighting use, combining dimming controls with manual on/off controls is rather effective if occupants generally sit in their offices most of the day. Research limitations/implications: – Precise comparisons of the performances of the different controls were limited due to the offices' different window orientations; thus, measurements in identical offices are desirable. The small sample size limited analyses of lighting use and the personal perceptions of lighting quality. Practical implications: – Apart from the contribution to simulation techniques, the findings imply that office lighting controls should be selected taking individuals' behavioural patterns and perceived lighting quality into consideration. Originality/value: – This paper describes an approach to determine the use of lighting controls and provides a basis for establishing optimal lighting use for individuals with regard to occupancy and daylight availability.